Boosting anodic methanol upgrading over RuO2 through integration with CeO2 for energy-saving H2 generation in acidic environment. (10th August 2022) - Li, Mengnan; Zhang, Dafeng; Yi, Yunfei; Xue, Bingjie; Liu, Baozhong
Highlights: An exciting electrocatalytic CH3 OH-to-HCOOH conversion is achieved on CeO2 /RuO2 in acidic media. The HCOOH selectivity maintains at a high level in a wide potential window. The reaction potential is significantly negative to that of oxygen evolution reaction on commercial RuO2 . Oxygen vacancies and high-valence Ru species contributed more to this oxygen uptake conversion. The reaction is a promissing anodic candiate for an energy-saving H2 generation by acidic water splitting. Abstract: Electrocatalytic hydrogen production by splitting water under acidic condition is still hindered by the excessive energy consumption due to the high overpotential of anodic oxygen evolution reaction (OER). Here an exciting methanol oxidation reaction (MOR) to formic acid in acidic media is achieved on CeO2 /RuO2 . The reaction contributes to a reaction potential as low as 1.195 V in half cell and a cell voltage reduction to 1.308 V in full cell when paralleling with Pt/C cathode at 10 mA cm −2, about 300 mV and 260 mV lower to the ordinary OER and overall water splitting by using pure RuO2, respectively. The production of formic acid reaches to a selectivity above 50% in a wide potential window with a top partial current density of formic acid up to 49.8 mA cm −2 at 1.52 V. The results generally demonstrate a promising application of MOR on CeO2 /RuO2 in the substitution for OER to achieve an energy-saving H2 generation via acidic water splitting. Mechanism insights reveal that CeO2 /RuO2 contains abundant oxygen vacancies and high-valence Ru species caused by the strong electronic interaction between the two subparts, which can greatly improve the water dissociation and the subsequent hydration of MOR intermediates, thereby favoring a non-CO pathway of MOR on CeO2 /RuO2 . Graphical abstract: Image, graphical abstract